2010
DOI: 10.1111/j.1751-0813.2010.00565.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive efficiency of Thoroughbred and Standardbred horses in north‐east Victoria

Abstract: On-farm pregnancy rates in both breeds were higher than previously reported and likely reflect improvements in reproductive management. The disparity between breeds in the inseminations per cycle and proportion of barren mares exposed the differing structures of the two industries, and presents a target for improving the reproductive efficiency in STBs. The difference between breeds in the multiple pregnancy rate per cycle likely reflects the higher ovulation rate of TB mares. The variability in pregnancy rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
65
6
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(91 citation statements)
references
References 22 publications
11
65
6
2
Order By: Relevance
“…; Nath et al. ). Coverings of young (3–8 years), middle aged (9–13 years), older mares (14–18 years) and mares aged 19 years and older resulted in per cycle pregnancy rates of 72%, 68%, 59% and 47%, respectively, with the oldest mares 2.87 times more likely to be not pregnant per cycle compared with the youngest mares.…”
Section: Discussionmentioning
confidence: 98%
“…; Nath et al. ). Coverings of young (3–8 years), middle aged (9–13 years), older mares (14–18 years) and mares aged 19 years and older resulted in per cycle pregnancy rates of 72%, 68%, 59% and 47%, respectively, with the oldest mares 2.87 times more likely to be not pregnant per cycle compared with the youngest mares.…”
Section: Discussionmentioning
confidence: 98%
“…Nath et al . reported significantly fewer embryonic losses between 13 and 45 days of gestation in mares diagnosed with multiple pregnancies that underwent manual elimination (4.6%) than in singleton pregnancies (7.5%), leading these authors to conclude that manual reduction should not adversely affect the remaining conceptus within 45 days of gestation . Given that the study by Nath et al .…”
Section: Discussionmentioning
confidence: 97%
“…This represents an improvement over the previously reported conception rates (ranging between 0 and 13% [1,2]) obtained using sex-sorted, cryopreserved stallion sperm. Around 7.5% of all conceptions in mares ('natural' or AI) result in EED [36], with 63% of these losses occurring between 15 and 45 days after ovulation. It has previously been shown that cold storage of stallion semen for 12-24 h prior to freezing is not detrimental to sperm motility or to conception rates as assessed by ultrasonography 15 days after insemination [4,[24][25][26] and that liquid storage of sperm either prior to or following sorting also does not appear to be appreciably detrimental to conception rates [4,27] or sperm quality [28].…”
Section: Discussionmentioning
confidence: 99%